2013
DOI: 10.1038/onc.2013.438
|View full text |Cite
|
Sign up to set email alerts
|

Merlin sumoylation is required for its tumor suppressor activity

Abstract: Merlin, encoded by the Neurofibromatosis 2 (NF2) gene, is a multifunctional tumor suppressor that integrates and regulates extracellular cues and intracellular signaling pathways, both at the plasma membrane and in the nucleus, to control cell proliferation, migration and invasion. Molecular mechanisms regulating merlin's tumor-suppressive activity have not been clearly defined. Here we report that merlin can be sumoylated on Lysine residue (K76) in vitro and in vivo. Sumoylation mediates merlin's intramolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Observation that the dephosphorylated form of Merlin preferentially translocates to the nucleus while the phosphorylated form is largely excluded is consistent with the long‐standing observation that Merlin suppresses tumorigenesis in its dephosphorylated form [27,29,32,49]. Moreover, several reports have characterized Merlin's localization in the nucleus, and Merlin migrates towards the nucleus by microtubule‐based transport in Drosophila [57,75,79,80]. Although Merlin lacks a canonical nuclear localization sequence, it contains a motif on its carboxy‐terminus that promotes nuclear export by the CRM1‐exportin pathway [80], and truncations that remove these residues show increased nuclear localization [29,32].…”
Section: Merlin Localization and Functionsupporting
confidence: 83%
See 1 more Smart Citation
“…Observation that the dephosphorylated form of Merlin preferentially translocates to the nucleus while the phosphorylated form is largely excluded is consistent with the long‐standing observation that Merlin suppresses tumorigenesis in its dephosphorylated form [27,29,32,49]. Moreover, several reports have characterized Merlin's localization in the nucleus, and Merlin migrates towards the nucleus by microtubule‐based transport in Drosophila [57,75,79,80]. Although Merlin lacks a canonical nuclear localization sequence, it contains a motif on its carboxy‐terminus that promotes nuclear export by the CRM1‐exportin pathway [80], and truncations that remove these residues show increased nuclear localization [29,32].…”
Section: Merlin Localization and Functionsupporting
confidence: 83%
“…Moreover, the importance of the ubiquitin–proteasome system in Merlin's degradation is debatable, as cycloheximide chase experiments revealed that Merlin has a half‐life exceeding 24 h [29], although this does not rule out other ubiquitination‐mediated effects on Merlin function. Akt‐ and PAK‐mediated phosphorylation of Merlin was recently shown to promote its sumoylation – an ubiquitin‐like modification – which was found to affect Merlin's subcellular localization, interdomain binding, and growth‐inhibitory activity [57]. However, the requirement for sumoylation in Merlin's normal function and in tumor suppression remains incompletely understood since serine 518 phosphorylation, which renders Merlin inactive, appears to promote its sumoylation.…”
Section: Post‐translational Modification Of Merlinmentioning
confidence: 99%
“…More recent work has demonstrated that NF2 is also a substrate of sumoylation. It was reported that SUMO-1 modification at Lys76 led to decreased active conformation status, altered subcellular localization, and impaired tumor suppressor function suggesting that sumoylation is important for proper NF2 signaling 41 . Whether or not NF2 is sumoylated in cardiomyocytes, and if this modification modulates NF2 activity in the heart, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since phosphorylation can promote SUMOylation 32 33 34 and TARBP2 phosphorylation by MAPK/Erk enhances its stability 19 , it is possible that phosphorylation might also regulate TARBP2 SUMOylation. As there are four major sites of phosphorylation by the MAPK/Erk pathway, S142, S152, S283 and S286 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%